Evaluasi Program Wajib Belajar 9 Tahun Pada Sekolah Negeri dan Sekolah Swasta (Studi Kasus di Sekolah Dasar Negeri dan Sekolah Dasar Muhammadiyah di Kota Yogyakarta) - Iyan Fathul Khoeriyah; Achmad Nurmandi (Universitas Muhammadiyah Yogyakarta, 2014)
The research aimed to acknowledge the evaluated of compulsory 9-year assurance in state elementary school (SDN)and private elementary school (Muhammadiyah) in the city of Yogyakarta. Data Analysis Unit in this research is headeducation section in elementary school at the city of Yogyakarta, head master, teacher, scholl committee and students,4 from state elementary school (SDN) and 4 from private elementary school (Muhammadiyah) in the city of Yogyakar ta.This research used method with data collection from the data analysis process based on the result of in depthinterview and documents. This study used descriptive and qualitative data with grounded theory method. The re-search result is the number of suitably qualified educational personnel do not achieve the target of only 40%. Thenthe number of students who were subjected to compulsory quota admission of new students in SDN and elementaryschools still have not meet the target. Facilities and infrastructure and Private Elementary School has not fully meet theprescribed standards, and sources of funding / budget, State elementary school (SDN) funding sourced from Re-gional Government Budget (APBD)and State Budget (APBN). While private elementary school funding sourced fromRegional Government Budget (APBD)and State Budget (APBN) and from (donations parents, fees, dues Sacrifice,building development money, charity / special assistance). Elementary School does not collect tuition while still attract-ing private primary schools charge tuition of students for a nominal amount of each school is different. The averagevalue of private elementary school graduation is more higher than the state elementary school (SDN). Increase(CCDMA) in the city of Yogyakarta is equal to 92% have been achieved target And (APTs) are on state elementaryschool (SDN) Patangpuluhan by 0,01% and the SD Muhammadiyah Purwodiningratan 1 by 0,01%.